Autoimmune hemolytic anemia warm-antibody type (Warm AIHA) in an 8-year-old Balinese girl - Yasa, Putu Tri; Mudita, Ida Bagus; Santoso, Hendra; Suraatmadja, Sudaryat (Paediatrica Indonesiana, 2017)
A case of autoimmune hemolytic anemia warm antibody type A (warm AIHA) in an 8-year-old Balinese girl was reported. The diagnosis was established based on clinical features, laboratory findings including positive Coombs’ Â test positive. The etiology was probably primary or Idiopathic. The child was transfused with packed red cells and treated with oral prednisone. The response of the treatment was good and she experienced complete remission. The prognosis in patients with idiopathic warm AIHA are unpredictable. The girl underwent further follow-up in the child hematologic division every two weeks.